Factors influencing child fostering practices in Bayelsa State, Nigeria. (2015)
This study examined child fostering practices in Bayelsa State as a way of understanding the influence of socio-economic and cultural factors on critical family decisions. Functionalism, Social Action and Rational Choice perspectives provided the theoretical anchor upon which the thematic phenomenon was discussed. Quantitative data were collected from 408 questionnaire respondents. Six In-depth Interviews (IDIs) and two Focus Group Discussions (FGDs) were conducted among biological and foster parents. The mean age of the respondents was 32.5±10.8 years. More than half of the respondents had negative perception about child fosterage; poverty, desire to have children enrolled in school, effective training of fostered children, death of parents, and marital separation are implicated in the decision by families to have their children fostered. Despite the influence of modernism, the practice has remained virile in Bayelsa state due to persistent high fertility, poverty and its traditional and symbolic significance among other reasons.